A Novel Approach to Enhancing the Effectiveness of Chemistry Teaching by Preservice Teachers - Meirbekov, Akylbek; Berdi, Dinara; Burayeva, Zhanat; Ikramov, Ilyas; Sarbaeva, Makpal (Ital Publication, 2025)
The objective of this article is to develop a new approach for improving the effectiveness of chemistry teaching, which involves transforming the teaching process via the use of interactive digital technologies. The research methodology is based on the Self-Determination Theory (SDT) and the Stimulus-Organism-Response (SOR) model. The study explores key constructs such as Perceived Usability (PU), Perceived Autonomy (PAU), Perceived Teaching Support (PTS), Perceived Competency (PCM), Perceived Relatedness (PRT), Perceived Ease of Use (PEOU), Cognitive Teaching Involvement (CTI), and Affective Teaching Involvement (ATI), examining their influence on teaching performance. Data were collected from 254 preservice chemistry teachers trained at Akhmet Yassawi International Kazakh-Turkish University, Kazakhstan. Structural equation modeling (SEM) was applied to test the scientific hypotheses. The findings showed that PU, PEOU, PAU, and PTS have a significant effect on CTI and ATI, which in turn have a positive effect on teaching effectiveness. In other words, the study confirms the importance of user-friendly and effective digital tools in developing positive attitudes towards technology adoption. The novelty of this paper comprises the author's concept of the educational process transformation through the usage of interactive digital technologies, which increases the chemistry education effectiveness. Doi: 10.28991/ESJ-2025-09-01-04 Full Text: PDF